Pengaruh Umur Dan Status Perkawinan terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kabupaten Tanah Datar - Wulan Sari Fadilla; Syamsir Syamsir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aimed to determine the effect of age and marital status on the performance of the village government apparatus in the village financial management in Tanah Datar District.The background of this study was that there were still a number of problems in village financial management that were influenced by factors of age and marital status.This research is a quantitative study with a population of 600 village government apparatus,. The sample of this study consisted of 248 determined by the Slovin formula, as well as the research sampling technique using the stage random sampling technique. Data in this study were collected through questionnaires. Data analysis in this study used descriptive analysis methods, t test, and ANOVA test. The results of this study indicate that there was no influence of age and marital status on the performance of the village government apparatus in the village financial management in Tanah Datar District.